The Efforts of the Regional Tax and Retribution Management Agency of Bungo Regency in Regulating Billboards to Increase Local Own-Source Revenue (PAD) Based on Regional Regulation No. 1 of 2024 (A Case Study in Bungo Barat Urban Village, Pasar Muara Bungo District, Bungo Regency) - Joko Setyoko; Ridwan; Aldi Ramadani (Jurnal Ragam Pengabdian, 2026)
This study analyzes the efforts of the Regional Tax and Retribution Management Agency (BPPRD) of Bungo Regency in regulating illegal billboards to increase Local Own-Source Revenue (PAD) based on Regional Regulation No. 1 of 2024, focusing on Bungo Barat Urban Village. A qualitative descriptive approach was employed, utilizing in-depth interviews with 12 informants from BPPRD, DPMPTSP, Satpol PP, billboard business operators, and local residents, supplemented by field observations and analysis of official documents. Key efforts include Whole of Government (WoG) synergy with related agencies, formation of a PAD oversight team, monthly field patrols 2-3 times, intensive socialization four times annually via door-to-door and Q&A seminars, and progressive sanctions ranging from "unpaid" stickers, 1% monthly administrative fines, to asset seizures by certified bailiffs in coordination with the Prosecutor's Office. Significant challenges encompass low taxpayer compliance (only 50% compliant), limited technical facilities for dismantling high-elevation billboards, and unresponsiveness of out-of-area vendors. PAD realization from billboard taxes rose from Rp1.53 billion in 2022 to Rp1.46 billion in 2024, achieving 96% of the overall Rp4.58 billion target for 2022-2024. Recommendations include developing a digital permitting application, procuring independent billboard dismantling equipment, and incentives for compliant taxpayers to reach 100% PAD targets.